Comparative study of the outcome of surgical decompression in Ludwig’s angina by conventional skin incision versus multiple interrupted skin incisions - Rao, Kulkarni Manik; P., Navneeth T.; S., Vivek; Rathod, Sonu S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Ludwig’s angina is a potentially life threatening infection characterized by a rapidly progressing, bilateral gangrenous cellulitis of all the three primary mandibular spaces namely submental, submandibular and sublingual. If left untreated the cellulitis can progress swiftly to produce obstruction of airway and death. Despite that, no specific guidelines exist and management is greatly dependent on clinical judgement and experience. Methods: Forty cases of patients with Ludwig’s angina, attending the department of otorhinolaryngology were included in this study and were randomly allocated into conventional incision (CI) and multiple incisions (MI) groups. Following informed written consent, either conventional incision or multiple small incisions were used for drainage and the outcomes analysed. Results: The mean age of patients was 28.4 years and majority of the patients belonged to 20-40 years age group. Male to female ratio was 2.3:1.The most common etiology was odontogenic. The outcome of both the conventional group and multiple small incisions group were comparable. The mean hospital stay of the conventional group was 10.25 days and multiple incisions group was 5.31 days which was statistically significant. Conclusions: Multiple small incisions for the drainage of Ludwig’s angina is a safe and less invasive alternative method, with the advantages being shorter hospital stay and better cosmesis without an increase in complications.